Adaptación, estandarización y validación de la escala multidimensional de ansiedad MASC en niños y adolescentes peruanos - Vivar Cuba, Roxana (2006)
The purpose of this study was to establish the adaptation standardization, reliability and validation of MASC for Peruvian children and adolescents. The sample involved 2104 children and adolescents, male and female, whose ages ranged from 7 and 17 years, from public and private schools of urban areas of the city of Lima and from representative cities of the three regions of Perú (Huamanga, Cajamarca, Cuzco, Chiclayo, Lima, Iquitos and Tarapoto) and 119 children and adolescents with diagnosis of anxiety, looked after in the NIMH Honor Delgado Hideyo Noguchi. The reliability estimated by the Cronbach Alpha was acceptable for the sub scales and the total. The MASC showed good construct validity and clinic, new qualification parameters through quartiles were established. The sensibility of the test Was of 87% and the specificity of 83 %.